2020
DOI: 10.1088/1674-1056/aba608
|View full text |Cite
|
Sign up to set email alerts
|

An efficient inverse approach for reconstructing time- and space-dependent heat flux of participating medium*

Abstract: The decentralized fuzzy inference method (DFIM) is employed as an optimization technique to reconstruct time- and space-dependent heat flux of two-dimensional (2D) participating medium. The forward coupled radiative and conductive heat transfer problem is solved by a combination of finite volume method and discrete ordinate method. The reconstruction task is formulated as an inverse problem, and the DFIM is used to reconstruct the unknown heat flux. No prior information on the heat flux distribution is require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…IHTPs originally emerged in the late 1950s when it was found that the aerodynamic heating of space vehicles is so high during re-entry to the atmosphere that the surface temperature of the thermal shield cannot be measured directly using temperature sensors. Since then, IHTPs have been used to estimate all kinds of unknown quantities [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], including, among others, initial/boundary conditions, source terms, geometry, heat flux, and thermophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…IHTPs originally emerged in the late 1950s when it was found that the aerodynamic heating of space vehicles is so high during re-entry to the atmosphere that the surface temperature of the thermal shield cannot be measured directly using temperature sensors. Since then, IHTPs have been used to estimate all kinds of unknown quantities [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], including, among others, initial/boundary conditions, source terms, geometry, heat flux, and thermophysical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Tapaswini et al [25] used a variational iteration method (VIM) to reconstruct the boundary heat flux. Sun et al [26] employed the decentralized fuzzy inference method (DFIM) to estimate the time-and space-dependent heat flux of two-dimensional (2D) participating medium.…”
Section: Introductionmentioning
confidence: 99%